ANALISIS JASA LINGKUNGAN TAMAN PAKUJOYO, KABUPATEN SUKOHARJO, JAWA TENGAH - Ratna Widyaningtyas; Rosi Nur Safitri; Wahyu Kisworo (Yayasan Nusantara Hasana Berdikari, 2023)
Pakujoyo Park is one of the green open spaces in Sukoharjo Regency. Every green open space has potential environmental services, namely those provided by ecosystem functions whose benefits can be felt directly or indirectly. In this study, an analysis was carried out to determine the potential and function of environmental services from Pakujoyo Park including provisioning services, regulatory services, cultural services, and supporting services. Using data collection methods with questionnaires and interviews then carried out an analysis with a qualitative descriptive approach. The results showed that the characteristics of the respondents indicated the purpose of visitors to come to Pakujoyo Park. Its existence provides 4 environmental services including provision of services with the benefits of food crops, building material plants, shade plants, and ornamental plants. Then the regulatory service potential is in the form of the benefits of plants as water storage, air purification facilities, providing a sense of comfort, coolness, and shade, being able to withstand strong winds, as preventing erosion and flooding, being able to contribute as a barrier to climate change, and providing clean water. Pakujoyo Park cultural services in the form of recreational facilities indicated by the purpose of visiting almost all respondents is recreation. Supporting services in this park are in the form of benefits as a producer of oxygen from all existing plants, a place for habitat for various types of flora and fauna, protecting germplasm, and supporting plant pollination and nutrient cycles.